2010
DOI: 10.1002/jssc.200900855
|View full text |Cite
|
Sign up to set email alerts
|

A molecularly imprinted monolith for the fast chiral separation of antiparasitic drugs by pressurized CEC

Abstract: Molecularly imprinted polymer (MIP) monoliths with (S)-ornidazole ((S)-ONZ) as the template molecule have been designed and prepared by the simple thermal polymerization of methacrylic acid, 4-vinylpyridine, and ethylene dimethacrylate in the presence of a binary porogenic mixture of toluene and dodecanol. The influences of polymerization mixture composition on the chiral recognition of ONZ have been evaluated, and the imprint effect in the optimized MIP monolith has been clearly demonstrated. The new monolith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…In the first method, chiral template (L or D isomer) is utilized in the polymerization stage [9,11] and in the second way chiral template is replaced with chiral functional monomers [1,32]. In this work, we utilized the first synthesis strategy.…”
Section: Synthesis Of Chiral Imprinted Polymer and Its Characterizationmentioning
confidence: 99%
“…In the first method, chiral template (L or D isomer) is utilized in the polymerization stage [9,11] and in the second way chiral template is replaced with chiral functional monomers [1,32]. In this work, we utilized the first synthesis strategy.…”
Section: Synthesis Of Chiral Imprinted Polymer and Its Characterizationmentioning
confidence: 99%
“…Recently, Li et al 116 reported the preparation of MIP monolith using the L ‐enantiomer of amino acid as the template molecule and investigated the chiral recognition of MIP monolith in pCEC. MIP monoliths with ( S )‐ornidazole (( S )‐ONZ) as the template molecule have been designed and prepared by the simple thermal polymerization of MAA, 4‐VP and EDMA in the presence of a binary porogenic mixture of toluene and dodecanol 117. The enantiomers were rapidly separated within 9 min on the MIP‐based chiral stationary phase by pCEC (Fig.…”
Section: Cec Using Molecularly Imprinted Monolithmentioning
confidence: 99%
“…Due to high selectivity of MIP and high performance of CEC, MIP capillary monolith is usually used as the chiral stationary phase in the CEC mode, especially for separation of chiral drugs 108, 111–114, 116, 117, 123, 125–130. Simultaneously, MIP could also be used for the separation of positional isomers or structural analogues, which can be used to remove small amounts of impurities or isolate one of the expensive isomers or analogues 131–135.…”
Section: Cec Using Molecularly Imprinted Monolithmentioning
confidence: 99%
“…Liao et al [19] designed and prepared several molecularimprinted polymer monoliths with S-(−)-ornidazole as a template molecule for the rapid chiral separation of ornidazole enantiomers by pressurized capillary electrochromatography. They found that the chiral separation of secnidazole enantiomers was also achieved within 14 min using an optimized monolith.…”
Section: Introductionmentioning
confidence: 99%